Prabowo's Nutritious Meals: Key to Sustainability of Food Estate Program - Ompusunggu, Dicky Perwira; Suherman, Suherman; Rakhmawati, Dewi; Nasrida, Muhammad Farras; Simbolon, Tiur Roida; Husnatarina, Fitria (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
The Food Estate program was initiated to support national food security by enhancing food production on peatlands. However, its implementation faces various challenges, including difficult land conditions and the need for adequate infrastructure. This study aims to identify key factors influencing the sustainability of the Food Estate program in Central Kalimantan, particularly in the Kapuas and Pulang Pisau districts. This study employs the MICMAC method (Matrix of Crossed Impact Multiplications Applied to a Classification) to analyze the impact of strategic variables, such as government policy, infrastructure, institutional support, and local economy. The findings indicate that government policy and infrastructure support are dominant factors affecting the program's success, while variables like local economy and farmers’ income heavily depend on these factors. Recommendations include the need for sustainable policy enhancement, development of supporting infrastructure, improved market access, and adaptive technology training for farmers. With optimal implementation, the Food Estate program is expected to not only enhance national food security but also foster economic growth and improve the welfare of local communities in Central Kalimantan.